The linkage between individual value and knowledge creation in human capital - Kusumawijaya, Ida Ketut; Astuti, Partiwi Dwi (Business: Theory and Practice, 2023)
This study aims to examine the relationship between individual value and knowledge creation in human capital.The effect of individual value on each element of knowledge creation – socialization, externalization, combination and internalization – is tested in this study. The study also tested the effect of each component of knowledge creation with human capital. Data were collected using an online questionnaire. A total of 286 questionnaires were sent to managers of medium-sized companies in the province of Bali, Indonesia. Of the 196 questionnaires that were sent, returned and filled out completely, 158 had responses that were utilizable, showing a usable response rate of 80.61%. Data analysis was carried out using variance-based structural equation modelling with a partial least squares approach (SEM-PLS) with WarpsPLS 7.0. The results of the study found a significant positive effect of individual value on each element of knowledge creation: with socialization, with externalization, with combination and with internalization. This study also found that each component of knowledge creation has a significant positive effect on human capital: socialization, externalization, combination and internalization, respectively. This study shows that the value that is believed by individuals based on knowledge can be a strong factor of competitiveness for future of human capital.